2020
DOI: 10.1093/nar/gkaa523
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of antisense oligonucleotides modulating the activity of TLR7/8 agonists

Abstract: Oligonucleotide-based therapeutics have become a reality, and are set to transform management of many diseases. Nevertheless, the modulatory activities of these molecules on immune responses remain incompletely defined. Here, we show that gene targeting 2′-O-methyl (2′OMe) gapmer antisense oligonucleotides (ASOs) can have opposing activities on Toll-Like Receptors 7 and 8 (TLR7/8), leading to divergent suppression of TLR7 and activation of TLR8, in a sequence-dependent manner. Surprisingly, TLR8 potentiation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 45 publications
2
33
2
Order By: Relevance
“…Data shown are averaged from two independent experiments in biological triplicate (± s.e.m and ordinary one-way ANOVA with Tukey's multiple comparison tests to the ‘ISD70 only’ condition, or otherwise indicated pairs of conditions are shown). There was no basal effect of the ASOs on NT cells ( 21 ). ( C ) HT-29 cells pre-treated overnight with 125, 250 or 500 nM of indicated ASOs, were transfected or not (non-treated [NT]) with 2.5 μg/ml of ISD70 for 24h, and IP-10 levels in supernatants were determined by ELISA.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Data shown are averaged from two independent experiments in biological triplicate (± s.e.m and ordinary one-way ANOVA with Tukey's multiple comparison tests to the ‘ISD70 only’ condition, or otherwise indicated pairs of conditions are shown). There was no basal effect of the ASOs on NT cells ( 21 ). ( C ) HT-29 cells pre-treated overnight with 125, 250 or 500 nM of indicated ASOs, were transfected or not (non-treated [NT]) with 2.5 μg/ml of ISD70 for 24h, and IP-10 levels in supernatants were determined by ELISA.…”
Section: Resultsmentioning
confidence: 98%
“…Unexpectedly, we demonstrated that the majority of the 2′OMe gapmer ASOs tested were potent inhibitors of TLR7, but that selected sequences harbouring 2′OMe ‘CUU’ motifs did not block TLR7 activation ( 21 ). Conversely, we found that TLR8 sensing of the low molecular weight synthetic ligand Resiquimod (referred to as R848 hereafter), was potentiated by select 2′OMe ASOs, in a sequence-dependent manner, an observation that aligns with previous findings with poly-dT PS ODNs ( 21–23 ). These findings prompted us to investigate the broader immunomodulatory effects of 2′OMe ASOs on nucleic sensing, with the aim of defining the molecular patterns controlling these activities.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the past, many studies have focused on developing TLR7 agonists to activate host inflammatory responses to cope with RNA virus infections ( Alharbi et al, 2020 ; Shah et al, 2016 ). For example, TLR7 agonists were shown to provide protection against influenza A virus-induced morbidity in mice ( To et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%